Acute B-cell lymphoblastic leukaemia presenting as acute hepatitis - Jenosha, I.; Kumanan, T.; Suganthan, N.; Sooriyakumar, T.; Pranja, G. (Sri Lanka College of Internal Medicine, 2025)
Acute lymphoblastic leukaemia (ALL) typically presents with symptoms of bone marrow failure. Acute hepatitis is a rare and atypical presentation. We report the case of a 16-years old healthy boy, who presented with elevated liver enzymes and jaundice. His Initial investigations ruled out common infectious aetiology of hepatitis. Despite symptomatic management, the patient had persistent bicytopenia, prompting further evaluation with bone marrow biopsy which confirmed CD10-positive B-cell ALL. This case report illustrates the importance of a pragmatic approach to a non-resolving hepatitis.
Keywords: Acute B-cell lymphoblastic leukaemia; Acute hepatitis